Research, production and use of stabilized fertilizers in China: pathways for green transition and sustainable development strategies - Rui LIU; Weifeng ZHANG; Tikun GUAN; Dongjia LI; Zhiping DUAN; Zixin ZENG; Jiawei LI; Kaitong WANG; Sen DU; Yang XU; Li GAO; Jiahuan LIU; et al. (Frontiers of Agricultural Science and Engineering)
Stabilized fertilizers, enhanced with urease or nitrification inhibitors, have emerged as pivotal tools for China’s agricultural green transition, balancing crop productivity, resource efficiency, and environmental sustainability. Globally, Germany and other EU countries have pioneered inhibitor-integrated fertilizer policies, driving emission reductions. Despite China’s later start, breakthroughs in local production, diversified formulations (covering six major fertilizer categories) and standardized systems have positioned it as a global leader, with 90% of the raw material capacity and 3 Mt annual output (4% of the total fertilizer production). Meta-analysis of over 900 trials (2014–2018) demonstrates stabilized fertilizers increase yields by 9.2%, nitrogen use efficiency by 11.2% and lower N2O emissions by 28.4% in staple crops. Field studies further reveal multifunctional benefits including 60% higher nitrogen efficiency, 60% emission cuts, 20%–50% fertilizer savings and enhanced climate resilience. To maximize impact, advancing technology innovation, refining application protocols and fostering cross-sector collaboration are critical. This paper provides strategic insights to accelerate China’s sustainable agriculture transition and global climate goals.